Analisis Faktor Perubahan Pemanfaatan Lahan Di Kecamatan Watang Pulu Kabupaten Sidrap - Risnawati k; Ikhsan Andi Muhammad (Universitas Muslim Indonesia, 2021)
This research is about factors affecting changes in land use in watang pulu district, sidrap regency. the main problem is what factors cause changes in land use. this problem is seen in the physical condition of land-use changes that occur in watang pulu district. thus, this study uses descriptive analysis by looking at the currently developing land-use system and identifying the developing land-use system around it and its suitability with existing land conditions, namely data analysis that aims to describe the state of the observation area or according to the data obtained in this study. the form of decomposition and analysis is carried out to consider the existing physical conditions at the research location to anticipate the development of land use that is not by the function of the land in the wanting pulu district.